2018
DOI: 10.1007/s12517-018-3860-4
|View full text |Cite
|
Sign up to set email alerts
|

Bias adjustment of satellite-based precipitation estimation using artificial neural networks-cloud classification system over Saudi Arabia

Abstract: Precipitation is a key input variable for hydrological and climate studies. Rain gauges can provide reliable precipitation measurements at a point of observations. However, the uncertainty of rain measurements increases when a rain gauge network is sparse. Satellite-based precipitation estimations SPEs appear to be an alternative source of measurements for regions with limited rain gauges. However, the systematic bias from satellite precipitation estimation should be estimated and adjusted. In this study, a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…However, for constructing CDFs in each CCS pixel (0.04 • ), or even a 1 • × 1 • box (as used by Yang et al [34]), sufficient samples are necessary, but rain gauges are sparse in mountainous and desert areas such as Iran. Therefore, using climate regions with homogenous precipitation patterns as employed in this study and other similar works [36] would be an appropriate method to overcome this restriction in similar areas. Furthermore, using climate regions revealed the distinguished effects of bias corrections in different climates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for constructing CDFs in each CCS pixel (0.04 • ), or even a 1 • × 1 • box (as used by Yang et al [34]), sufficient samples are necessary, but rain gauges are sparse in mountainous and desert areas such as Iran. Therefore, using climate regions with homogenous precipitation patterns as employed in this study and other similar works [36] would be an appropriate method to overcome this restriction in similar areas. Furthermore, using climate regions revealed the distinguished effects of bias corrections in different climates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the CDFs can be accurately approximated only for sufficiently large sample sizes. To enlarge the sample size in some gauge-scarce regions such as Saudi Arabia, which is an arid country with a sparse rain-gauge network, Alharbi et al [36] used the QM for climate regions instead of a 1 • × 1 • box region. Their results showed that using climate regions (CR) led to more accurate CDF matching and a better bias correction of the PERSIANN-CCS compared to cases without climate regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ameliorate the uncertainties, both precipitation correction and multi-source estimation approaches have been explored and applied for different regions. Here, we distinguish between (1) the conventional approach of exclusively relying on rain gauge observations [6,18,19] and (2) the more recent approach of incorporating additional explanatory variables [20][21][22][23] to correct precipitation estimates. The latter approach is the focus of the current study.…”
Section: Introductionmentioning
confidence: 99%
“…For PERSIANN, there is a consistent pattern of overestimation (Alharbi, Hsu, & Sorooshian, 2018;Behrangi et al, 2011;Y. Yang & Luo, 2014).…”
Section: Precipitation Estimation From Remotely Sensed Information Usingmentioning
confidence: 72%